Interprofessional Collaborative Practice: How Could Dentistry Participate?. Issue 5 (1st May 2018) - Cole, James R.; Dodge, William W.; Findley, John S.; Horn, Bruce D.; Kalkwarf, Kenneth L.; Martin, Max M.; Valachovic, Richard W.; Winder, Ronald L.; Young, Stephen K.
Abstract : There is a remarkable phenomenon occurring among health professionals: the development of ongoing, routine collaboration, both in educating the next generation of providers and in delivering care. These new approaches, commonly referred to as interprofessional education and interprofessional collaborative practice, have been introduced into academic health settings and delivery systems throughout the U.S. and the rest of the world; however, the full integration of dentistry in health care teams remains unrealized. In academic settings, dentistry has found ways to collaborate with the other health professions, but most practicing dentists still find themselves on the margins of new models of care delivery. This article provides a perspective on the history and context of the evolution of collaborative approaches to health care and proposes ways in which dentistry can participate more fully in the future.